Analisis Teknik Penerjemahan terhadap Kitab Al-Ushul Ats-Tsalatsah: Pendekatan Molina Dan Albir - Nurul 'Afifah; Tajudin Nur; Nurina Dyah Putrisari (The Arabic Education Department Postgraduate Programs, UIN Sultan Maulana Hasanuddin Banten in Partnership with PPJKBA Indonesia, 2024)
Translation acts as a bridge for knowledge transfer. Translators must be well-versed in translation, including translation techniques. In this study, we will explore which translation techniques are used in Al-Ushul Ats-Tsalatsah’s translation, according to Molina and Albir's theory, and which translation techniques are most frequently used. The aspiration is that the outcomes of this study can offer valuable insights to translators and researchers specializing in Arabic language, aiding them in choosing translation techniques for religious texts with the goal of reducing confusion in the translation process. This study employs descriptive qualitative research methods. From the examination of 170 pieces of data, the translator used 13 of the 18 translation procedures suggested by Molina and Albir, with a total frequency of use of 215 times. These techniques include: (1) amplification, (2) transposition, (3) borrowing, (4) literal translation, (5) linguistic compression, (6) established equivalent, (7) linguistic amplification, (8) particularization, (9) reduction, (10) description, (11) calque, (12) generalization, and (13) modulation. The amplification is the most commonly used since certain terms and information in the SL text that cannot be effectively understood unless they are complemented by additional information according to its function.